Síntese e avaliação da atividade antileishmania, antitumoral e anticolinesterásica de 1-fenilssubstituído-β-carbolinas contendo na posição -3 o núcleo 1,2,4-triazólico 4,5-dissubstituído - Brand, George (2015)
In the present work we synthetized and evaluated the antileishmanial, antitumor and anticholinesterase activities of 1-phenyl substituted β-carbolines bearing a 4,5-substituted 1,2,4-triazole at position-3. The 1-phenyl substituted 3-(4-amino-5-mercapto-1,2,4-triazol-3-yl) ?-carbolines (11), intermediates for the preparation of the proposed derivatives, were prepared by the Pictet-Spengler condensation, under acid catalysis, of L-tryptophan methyl ester with aromatic aldehydes, followed by oxidation of 3-carbomethoxy-tetrahydro-?-carbolines (64), to give the 3-carbomethoxy-?-carbolines (65). Treatment of 65 with hydrazine hydrate gave the ?-carboline-3-carbohydrazides 66, which afforded the 1-phenyl substituted 3-(4-amino-5-mercapto-1,2,4-triazol-3-yl) ?-carbolines (11) by intramolecular cyclization of their corresponding dithiocarbazates (67). The Schiff bases (76, 77, 79 e 80) were obtained from the condensation of 1-phenyl-3-(4-amino-5-thiomethyl-1,2,4-triazol-3-yl) ?-carboline (75) with aromatic aldehydes, under microwave irradiation, in DMF. The diazotization reaction, followed by cyclization, of the intermediates 11 with sodium nitrite, in acidic medium, afforded the 3-(1-substituted-9H-?-carbolin-3-yl)-1,2,4-triazolo[4,3-d]-1,2,3,4-thiatriazoles (14). The 3-(1-substituted-9H-?-carbolin-3-yl)-1,2,4-triazolo[3,4-b][1,3,4]thiadiazole-6-thiol/thiones (15) were prepared from the reaction of 4-amino-5-mercapto-1,2,4-triazoles (11) with carbon disulfide in sodium hydroxide as base. Attempts to introduce the fused heterocycle 1,2,4-triazolo-[3,4-b]-1,3,4-thiadiazin-6-one at position-3 of b-carboline nucleus by reaction of 11 with chloroacetic acid or ethyl bromoacetate afforded only the S-alkylated products. All compounds were characterized by their spectroscopic data (MS, 1H and 13C NMR and HSQC).Compounds 76, 77 and 79, and 14a-c, were evaluated for their antitumor activity in vitro against eight human tumor cell lines: lung (NCI-460), colon (HT-29), prostate (PC-3), breast (MCF-7), renal (786-0), glioma (U-251), resistant ovarian (NCI/ADR-RES), ovarian (OVCAR-3). All compounds showed potent activity against the tumor breast cells (MCF-7) with GI50 in the 2.07 to 4.75 ?M. The derivatives 11a-d were evaluated against promastigote forms of Leishmania amazonensis, being more active the derivative 11b, with GI50 of 6.98 ?M. The assays results for compounds 11ad towards acetylcholinesterase inhibition showed that all derivatives inhibited the enzyme with GI50 values in the range of 17,7 to 97,7?M